2017
DOI: 10.7570/jomes.2017.26.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Markers as Predictors for Colorectal Neoplasia

Abstract: Background The goal of this study was to determine the relations between the risk of colorectal neoplasia and obesity markers: body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR). Methods The subjects who underwent screening colonoscopies at a Kyungpook National University Hospital in Daegu from July to December 2010 were enrolled. We defined colorectal neoplasia as tubular adenoma, advanced adenoma, or cancer. We performed a logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
4
0
2
Order By: Relevance
“…However, the present observation is consistent with the report by Nattenmueller et al [25], who found that WHtR was a better predictor of adipose tissue compartments and SMM than BMI and waist-to-hip ratio (WHR), although, compared to the CT-based measurement, WHtR did not adequately capture differences according to age and gender. Nevertheless increased WHtR with different cut-offs is recognized as a risk factor and/or prognostic parameter in numerous clinical conditions, such as thyroid cancer (WHtR ≥ 0.5) [31], primary liver cancer [32,33], prostate cancer (WHtR > 0.59 or ≥ 0.6 [34]), gallbladder cancer [35], breast cancer [1,36], kidney cancer in postmenopausal women [37], all obesity-related cancers (WHtR ≥ 0.51 in men, and ≥ 0.57 in women) [1,38], CRC (WHtR ≥ 0.55 [39] or ≥ 0.5 [40]), and prognosis after CRC surgery [41]. Moreover, increased WHtR is a better predictor for the risk of metabolic disorders (diagnostic value in descending order: WHtR > WHR > WC > BMI) [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the present observation is consistent with the report by Nattenmueller et al [25], who found that WHtR was a better predictor of adipose tissue compartments and SMM than BMI and waist-to-hip ratio (WHR), although, compared to the CT-based measurement, WHtR did not adequately capture differences according to age and gender. Nevertheless increased WHtR with different cut-offs is recognized as a risk factor and/or prognostic parameter in numerous clinical conditions, such as thyroid cancer (WHtR ≥ 0.5) [31], primary liver cancer [32,33], prostate cancer (WHtR > 0.59 or ≥ 0.6 [34]), gallbladder cancer [35], breast cancer [1,36], kidney cancer in postmenopausal women [37], all obesity-related cancers (WHtR ≥ 0.51 in men, and ≥ 0.57 in women) [1,38], CRC (WHtR ≥ 0.55 [39] or ≥ 0.5 [40]), and prognosis after CRC surgery [41]. Moreover, increased WHtR is a better predictor for the risk of metabolic disorders (diagnostic value in descending order: WHtR > WHR > WC > BMI) [42].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the presence of pre-malignant lesions in obese patients, the proportion was higher than in individuals of normal weight or overweight, since 47.8% of this population had adenomatous lesions. Studies indicate that obesity is associated with an increase in the prevalence of benign colorectal neoplasia and, consequently, of CRC 13 , 15 , 23 . A meta-analysis conducted in westerners showed that the increase in BMI by 5 kg/m 2 increased the risk of colorectal adenomas by 1.19 times, and also by CRC by 1.13 and 1.06 times in men and women, respectively 19 .…”
Section: Discussionmentioning
confidence: 99%
“…O tecido adiposo em excesso observado na obesidade, bem como as mudanças anatômicas, provoca alterações que impactam o sistema digestivo de modo microscópico e global (NAM, 2017). Sobrepeso e obesidade estão envolvidos no aumento do risco de um amplo espectro de doenças digestivas, como doença do refluxo gastroesofágico, esôfago de Barrett, esofagite erosiva, doença hepática gordurosa não alcoólica, cálculos biliares e pancreatite, além de cânceres de órgãos digestivos, como colangiocarcinoma, carcinoma hepatocelular, câncer pancreático, câncer colorretal e câncer de esôfago (FUJIHARA et al,2012;KWON et al, 2017;TAHERGORABI et al, 2018).…”
Section: Introductionunclassified